Enhancing treatment outcomes after gynaecological cancer (ACUMEN): a randomised controlled exercise trial protocol - Vivian Chiu; Alexander Boytar; Brent Cunningham; Tina Skinner; Jane Turner; Debra Anderson; Asaduzzaman Khan; Tom Bailey; Janine Porter-Steele; Leonie Young; Haitham Tuffaha; Lewis Perrin; et al. (BMC Cancer)
Abstract Background Treatment for gynaecological cancer often entails challenges that negatively affect quality-of-life. While exercise has been shown to improve physical and psychosocial well-being during cancer recovery, affected women often avoid exercise due to the specific health challenges they face after treatment. The Enhancing treatment outcomes after gynaecological cancer (ACUMEN) program aims to enhance health-related quality of life in this group by promoting lifelong exercise habits. Methods The ACUMEN trial is a single-blind, multi-centre randomised controlled trial that evaluates the impact of a structured exercise intervention on quality of life in women who have completed primary treatment for gynaecological cancer within the last 60 months. A total of 342 participants will be randomly assigned to either usual care or an intervention group. The intervention involves a 12-week personalised exercise program, where participants will complete three 1-h exercise sessions per week. During the first six weeks, participants will receive two supervised sessions with accredited exercise physiologists or physiotherapists and self-manage one session per week. In the following six weeks, this shifts to one supervised session and two self-managed sessions weekly, with goal of fostering sustainable, self-managed exercise habits. Assessments will take place at baseline, Week 12 (end of intervention), and Week 24 (end of maintenance). The primary outcome is health-related quality of life, measured by the Short Form-36. Secondary outcomes include exercise self-efficacy, body composition, symptoms of lymphoedema, physical fitness, biological markers, and habitual physical activity levels. For intervention group participants assigned accredited exercise physiologists or physiotherapists will track attendance, adherence, feasibility, and safety. Discussion The ACUMEN trial will evaluate whether a structured exercise program improves health-related quality of life in women recovering from gynaecological cancer treatment. The findings will help determine if the intervention is effective and sustainable, with a simultaneous cost-effectiveness analysis conducted to assess its value for money. Results from this study could inform future exercise-based interventions to enhance cancer recovery. Trial registration Australian New Zealand Clinical Trial Registry (ACTRN12621000050853, registered 19/01/2021).